OHS Risk Management Using the Hirarc Method (Hazard Identification, Risk Assessment, and Risk Control) on Emu Maintenance Work at PT KCIC - Kumail Akhmad Sodik; Candra Pramua Pinandita (Pasca Sarjana UKI, 2025)
The Electric Multiple Units (EMU) owned by PT Kereta Cepat Indonesia China (PT KCIC) have a height of 4.05 meters, requiring maintenance to be performed at height. Furthermore, workers must climb onto the EMU and work in close proximity to high-voltage electrical systems, specifically the Overhead Catenary System (OCS) (Rahadian Ratry, 2023). To ensure that the production process continues while safeguarding workers, equipment, and the environment from occupational accidents, hazard identification must be conducted, as workplace conditions contain potential hazards that could endanger workers during maintenance. The hazard identification technique used in this study is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). Based on field investigations and studies conducted at the PT KCIC Joint Workshop, where EMU repair operations are performed, three categories of occupational hazards with ten potential risks were identified. Based on the risk assessment of the ten potential hazards, three risks are categorized as moderate, four as high, and three as very high. Risk control for potential hazards in EMU maintenance work is carried out following the completion of the hazard identification and risk assessment stages. The OHSAS 18001:2007 risk control hierarchy is utilized to implement control measures that reduce risks to manageable levels, considering solutions that align with the company's actual conditions